(untitled) (Research, Society and Development, 2022)
Organized this article by developing, initially, a brief presentation of the data on Technological Resources available in schools according to administrative dependence - Brazil - 2019, later we also present data on Technological Resources available in schools according to administrative dependence - Brazil - 2020 and Technological resources available in schools according to regions - Brazil - 2020. And finally, let’s see the difference between the year 2019 and 2020, we bring a theoretical discussion about the importance of technological resources in schools. Technological resources reach the most diverse areas of knowledge and are present in people’s daily lives. Therefore, we believe that teachers have a role to play in this process, which is to test existing tools and new ones that may arise in order to decide together with students, to what extent such resources are essential to facilitate and catalyze production and dissemination of knowledge.